The Influence of Personal Hygiene on the Prevalence of Soil-Transmitted Helminths (STH) in Children: A Case Series in a Remote Indigenous Community in Indonesia - Nur Laela Alydrus; Ka’bah; Rugayyah Alyidrus; Risky Nurul Fadlila RN; Fika Andriani (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Soil-transmitted helminths (STHs) are a major public health concern, especially in remote indigenous communities with limited access to clean water and sanitation. This study aimed to investigate the influence of personal hygiene practices on the prevalence of STH infections in children in the Ammatoa Kajang community of Bulukumba Regency, Indonesia. Methods: An observational case series was conducted among children aged 3-13 years in the Ammatoa Kajang community. Data on personal hygiene practices were collected through questionnaires and interviews, while stool samples were examined for STH infections using the Kato-Katz method. Data were analyzed using correlation tests to determine the relationship between personal hygiene and STH prevalence. Results: The prevalence of STH infection was 45%, with Ascaris lumbricoides being the most common (30%), followed by Trichuris trichiura (10%) and hookworm (5%). Poor personal hygiene practices, such as infrequent handwashing, not using soap after defecation, and not wearing footwear, were significantly associated with an increased risk of STH infection. Conclusion: Personal hygiene plays a crucial role in the prevalence of STH infections among children in the Ammatoa Kajang community. Health promotion programs focused on improving personal hygiene practices, along with improved sanitation facilities, are essential for reducing the burden of STH infections in this remote indigenous community.